Mandibular premolar transposition: A rare case report (Indian Journal of Case Reports, 2020)
Tooth transposition is one of the most difficult dental anomalies to treat in the dental clinic. The etiology of tooth transposition has been the subject of much controversy and is still not completely understood. Multifactorial genetic factors, an interchange in the position of the developing dental lamina of the involved teeth, and even trauma to the deciduous teeth in which dilacerations of the permanent incisor root was found have all been suggested as causes for transposition of teeth. The management of posterior tooth transposition is purely subjective until and unless the patient reported with some unstable occlusal patterns or functional insufficiency. This present case report with complete transposition of mandibular left second premolar erupted in the site of mandibular left first molar in a 42-year-old female patient is a rare case entity for clinical consideration.